STUDI OPTIMALISASI TATA KELOLA PEMERINTAHAN DI KECAMATAN LEMBANG (THE OPTIMIZATION STUDY of GOOD GOVERNANCE in LEMBANG): STUDI OPTIMALISASI TATA KELOLA PEMERINTAHAN DI KECAMATAN LEMBANG (THE OPTIMIZATION STUDY of GOOD GOVERNANCE in LEMBANG) - adibowo, rino (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2023)
Good governance is an implementation of solid and responsible development management that is in line with the principles of democracy with an efficient market, avoidance of misallocation of investment funds, and prevention of corruption both politically and administratively. Good governance is a concept that is widely discussed in political science and public administration, especially in relation to democracy, civil society, people's participation, human rights, and sustainable community development. In practice, good governance is a form of state and community management that relies on the interests of the people. The Lembang District is included in the agropolitan area and also urban tourism because it has the potential to develop the local economy which can help PAD (The Local Own-source Revenue) the local government of west Bandung. These potentials such as agriculture, plantations, animal husbandry and tourism, both natural and artificial tourism. The Lembang District has a fairly high agricultural sector, especially in vegetable commodities, where vegetable production in Lembang District has been exported to several countries and 70% supports Jakarta retailers, agriculture is spread in almost all villages in Lembang District. The research problem in Lembang District is regarding Disaster Prone. Lembang is one of the sub-districts that is included in the Lembang fault line which starts from Padalarang sub-district to Jatinangor which has a distance of about 29 KM. when viewed from the condition of the soil in the Lembang sub-district, it has loose soil which causes many landslides due to slope instability. This research is important to do to see how to optimize governance in Lembang District, especially in the agricultural and tourism sectors. The optimization study was identified based on the Regional Regulation of West Bandung Regency Number 4 of 2012 concerning the West Bandung Regency Tourism Development Master Plan. This research is expected to provide benefits and new knowledge regarding optimizing governance in Lembang District. Keywords: Good Governance, The Optimization, Urban Planning, Autonomous Region.